Influence Of Urban Design Principles And Physical Elements On Urban Design Quality In Merdeka Square, Medan, Indonesia - Fachrudin, Hilma Tamiami (2014)
Urban design quality is important in urban area since development process begins. Urban design quality contributes to an attractive urban area, suitable place to live, sustainable and has a sense. The factors that influence urban design quality are urban design principles and urban physical elements. Urban design principles can be used as guides to realize urban design quality. Urban design quality can be measured by people’s perception and the measurement will depend on the object and community characteristics. Research objectives are to identify application of urban design principles on physical elements and their influences on urban design quality. This research was performed in central of Medan city, North Sumatera Province, Indonesia. Research population are visitors who use pedestrian walkways during working days and on weekend within the study area with a total sample of 397 respondents. This research uses qualitative and quantitative methods and is performed with observation technique, semi-structured interview and questionnaire survey. Observation was conducted to find application of urban design principles on physical elements. Then, the application was analyzed with simple arithmetic calculation and formed into questions on questionnaire form. The survey with questionnaire was performed to get the perception of respondents about application of urban design principles on physical elements and urban design quality. Partial Least Square (PLS) analysis was used to analyze the influence of urban design principles on physical elements as independent variables and urban design quality and application of sense on physical elements as dependent variables. Semi-structured interviews were conducted to find the explanation from stakeholders, namely Medan City government officers about urban design quality. The results are used to confirm with the statistical analysis results. From the analysis results, it is found that the application of urban design principles on physical elements occur as deliberately planned or unplanned. The application can be divided into physical and nonphysical entities.